IMPLEMENTASI MATEMATIS SISTEM PENDAFTARAN PASIEN ONLINE DAN PEMERIKSAAN DOKTER MENGGUNAKAN METODE UEDP PADA RUMAH SAKIT ISLAM MALAHAYATI - Maurico Liang; Raissa Amanda Putri (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Malahayati Islamic Hospital, a private healthcare institution in Medan, North Sumatra, established in 1963 by the Malahayati Islamic Education Foundation, has a capacity of 100 beds and is committed to providing quality and affordable healthcare services. However, problems arose with the hospital's website, which did not provide online booking services and doctor's practice schedules. This makes it difficult for patients, especially those coming from out of town, and can result in long queues at registration. To overcome this problem, the author wants to build and implement a web-based Online Patient Registration System and Doctor Practice Schedule at Malahayati Hospital. It is hoped that this system will not only provide easy access for patients to view and register online but also help hospital admins in effective management of doctor schedules. The results of the study are expected to have a positive impact on the efficiency and quality of health services at Malahayati Islamic Hospital